Surfactant Utilization Evaluation in a Major Teaching Hospital in West of Iran: An Observational, Prospective Study - Sajad Khiali; Mohammadbagher Hosseini; Elnaz Shaseb (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: The respiratory distress syndrome (RDS) is a common pulmonary disorder that usually occurs as a result of preterm labor and is associated with lack of surfactant. The aim of this study was to evaluate the pattern of surfactant prescription in Alzahra teaching hospital in Tabriz, Iran. Methods: This drug use evaluation (DUE) study was conducted in the neonatal intensive care unit (NICU) of Al-Zahra Hospital, Tabriz, Iran. The demographic and clinical data collection was performed using clinical records of patients. The pattern of surfactant replacement therapy was evaluated and compared with the European Consensus Guideline on the management of respiratory distress syndrome in 2016. Results: A total of 252 premature infants who received surfactant between August 2017 and March 2018 were included. 80.8% of neonates were born by cesarean section. The most used surfactant was Curosurf®, which was used in 82.1% of cases. Only 34.9% of the infants received within 8 hours of birth. Moreover, 79% of infants received the standard dose of surfactant, while 9.5 % and 11.5% were given high and low doses of surfactant, respectively. Conclusion: The pattern of surfactant replacement therapy was not completely according to the guidelines, particularly regarding the time of administration.  Considering the importance of dose and timely administration of surfactant, providing strategies to decrease these errors are important.